Congruence between fine-scale genetic breaks and dispersal potential in an estuarine seaweed across multiple transition zones. (22nd November 2019) - Nicastro, Katy R; Assis, Jorge; Serrão, Ester A; Pearson, Gareth A; Neiva, João; Valero, Myriam; Jacinto, Rita; Zardi, Gerardo I
Abstract: Genetic structure in biogeographical transition zones can be shaped by several factors including limited dispersal across barriers, admixture following secondary contact, differential selection, and mating incompatibility. A striking example is found in Northwest France and Northwest Spain, where the estuarine seaweed Fucus ceranoides L. exhibits sharp, regional genetic clustering. This pattern has been related to historical population fragmentation and divergence into distinct glacial refugia, followed by post-glacial expansion and secondary contact. The contemporary persistence of sharp ancient genetic breaks between nearby estuaries has been attributed to prior colonization effects (density barriers) but the effect of oceanographic barriers has not been tested. Here, through a combination of mesoscale sampling (15 consecutive populations) and population genetic data (mtIGS) in NW France, we define regional genetic disjunctions similar to those described in NW Iberia. Most importantly, using high resolution dispersal simulations for Brittany and Iberian populations, we provide evidence for a central role of contemporary hydrodynamics in maintaining genetic breaks across these two major biogeographic transition zones. Our findings further show the importance of a comprehensive understanding of oceanographic regimes in hydrodynamically complex coastal regions to explain the maintenance of sharp genetic breaks along continuously populated coastlines.